2016
DOI: 10.1128/jcm.01447-15
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Phenotypic and Genotypic Approaches to Capsule Typing of Neisseria meningitidis by Use of Invasive and Carriage Isolate Collections

Abstract: e Neisseria meningitidis serogroup B (MnB) is a leading cause of bacterial meningitis; however, MnB is most commonly associated with asymptomatic carriage in the nasopharyngeal cavity, as opposed to the disease state. Two vaccines are now licensed for the prevention of MnB disease; a possible additional benefit of these vaccines could be to protect against disease indirectly by disrupting nasopharyngeal carriage (e.g., herd protection). To investigate this possibility, accurate diagnostic approaches to charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
30
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 92 publications
2
30
0
Order By: Relevance
“…This study was also only conducted at 3 time points and was not a continuous longitudinal sampling study, and so provides only a limited understanding of the dynamics of carriage changes in this population, and cannot provide information on transmission patterns. Additionally, many of the isolates were ungroupable, which has been seen before in carrier studies (Caugant et al, 2006;Celal Basustaoglu et al, 2011;Glitza et al, 2008;Korzeniewski et al, 2015;Tyski et al, 2001) and previous evidence has shown challenges in serogrouping of isolates from carriage studies due to reduced or no capsule expression in the carriage state (Jones et al, 2016). Similarly genetic plasticity of the capsule can effect PCR assay sensitivity (Jones et al, 2016) and may have resulted in some of the discrepancy seen between the assays.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This study was also only conducted at 3 time points and was not a continuous longitudinal sampling study, and so provides only a limited understanding of the dynamics of carriage changes in this population, and cannot provide information on transmission patterns. Additionally, many of the isolates were ungroupable, which has been seen before in carrier studies (Caugant et al, 2006;Celal Basustaoglu et al, 2011;Glitza et al, 2008;Korzeniewski et al, 2015;Tyski et al, 2001) and previous evidence has shown challenges in serogrouping of isolates from carriage studies due to reduced or no capsule expression in the carriage state (Jones et al, 2016). Similarly genetic plasticity of the capsule can effect PCR assay sensitivity (Jones et al, 2016) and may have resulted in some of the discrepancy seen between the assays.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, many of the isolates were ungroupable, which has been seen before in carrier studies (Caugant et al, 2006;Celal Basustaoglu et al, 2011;Glitza et al, 2008;Korzeniewski et al, 2015;Tyski et al, 2001) and previous evidence has shown challenges in serogrouping of isolates from carriage studies due to reduced or no capsule expression in the carriage state (Jones et al, 2016). Similarly genetic plasticity of the capsule can effect PCR assay sensitivity (Jones et al, 2016) and may have resulted in some of the discrepancy seen between the assays. MLST and whole genome sequencing (WGS) are more precise methods for characterizing isolates, however they were not used in this study to characterize all of the positive samples.…”
Section: Discussionmentioning
confidence: 94%
“…Grouping of carriage isolates is challenging whether using phenotypic or genotypic approaches. High percentages of isolates recovered from healthy carrier's displays low level or complete absences of expression of the genes required for capsule production during carriage, this due to phase variation, deletions or insertion of genetic mobile elements or a complete absence of the capsule genes .…”
Section: Discussionmentioning
confidence: 99%
“…It would be of interest to analyze the data from this study with respect to the presence of the genes encoding NHBA, NadA, and fHbp. Similarly, the data of Jones et al (11) could also provide clues as to why MenB strains, in particular, seem to express their polysaccharide capsule less avidly during carriage. This could be the result of a combination of phase variation and deletions or insertions in the cps locus.…”
mentioning
confidence: 97%
“…This lack of sensitivity has potential implications for the surveillance of meningococcal carriage following vaccination with the novel MenB vaccines. In this issue, Jones and coworkers present the results of their comparative study of phenotypic and genotypic approaches to N. meningitidis capsule typing (11). The investigators looked at invasive (n ϭ 97) and carriage (n ϭ 93) isolates from different populations, geographic locations, and time periods.…”
mentioning
confidence: 99%